Wireless Power Transfer for UAV Applications: A Parametric Approach for Coupler Design - Terrah, Mohammed; Smail, Mostafa Kamel; Pichon, Lionel; Bensetti, Mohamed (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper explores Wireless Power Transfer (WPT) for Unmanned Aerial Vehicles (UAVs) battery recharging. To enhance the performance of WPT various parameters such as frequency, compensation topology, and the number of coils turns are examined. The objective is to identify the most suitable combination in terms of efficiency, weight, and feasibility. The aim of this procedure is to ensure a maximum WPT efficiency while having a minimum additional weight, thereby providing autonomous recharging processes, and extending the duration of the UAV mission. The analysis is carried out through simulations and measurements, taking into account the variations of the coupling factor due to potential lateral misalignment of the parallel coils.